Using horizontal sonic crystals to reduce the aeroacosutic signature of a simplified ICE3 train model. (15th January 2021) - Minelli, G.; Yao, H.-D.; Andersson, N.; Lindblad, D.; Forssén, J.; Höstmad, P.; Krajnović, S.
Abstract: The design of noise barriers for high-speed trains is challenging due to the flow interaction between the train body and barriers. A failed design could affect the flow that in turn introduces additional aerodynamic loads to the train and generates extra noise. This study is the first investigation to numerically explore the detailed effects of noise barriers on high-speed trains. In particular, horizontal sonic crystals are compared to vertical, closed at the ground barriers in order to investigate the detailed effects of different noise screens on high-speed trains. The compressible IDDES is used to simulate the flow. The focus of this study is twofold. The first is to test if an alternative barrier typology can effectively reduce the noise signature, without having an impact on the train's aerodynamic performance. The second is to explore the connection between the near-field velocity fluctuations and the far-field noise. A few specific tonal frequency components have been commonly reported but not clearly explained in the literature. It is unclear if the specific tonal components are less dependent on the Reynolds numbers, although, in general, energetic flow structures are dependent on inflow speeds. Concerning the noise reduction, the results show that the sonic crystal barrier case has a significantly better performance. A modal analysis is used to explore the causes of the tonal peaks and the association of the underbody swirling vortices to the far-field noise is described.